2022
DOI: 10.1371/journal.pcbi.1010578
|View full text |Cite
|
Sign up to set email alerts
|

mPPases create a conserved anionic membrane fingerprint as identified via multi-scale simulations

Abstract: Membrane-integral pyrophosphatases (mPPases) are membrane-bound enzymes responsible for hydrolysing inorganic pyrophosphate and translocating a cation across the membrane. Their function is essential for the infectivity of clinically relevant protozoan parasites and plant maturation. Recent developments have indicated that their mechanism is more complicated than previously thought and that the membrane environment may be important for their function. In this work, we use multiscale molecular dynamics simulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Our model provides, for the first time, an overall explanation of ion selectivity and catalysis in all M-PPases and makes testable predictions: e.g., global conformational changes should occur in the first 0.1–0.2 s at 20 °C. These need to be tested through functional and structural studies, in particular the use of time-resolved, single-molecule techniques to capture further details of mechanism, as well as molecular dynamics simulations—efforts that are already underway (Holmes et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our model provides, for the first time, an overall explanation of ion selectivity and catalysis in all M-PPases and makes testable predictions: e.g., global conformational changes should occur in the first 0.1–0.2 s at 20 °C. These need to be tested through functional and structural studies, in particular the use of time-resolved, single-molecule techniques to capture further details of mechanism, as well as molecular dynamics simulations—efforts that are already underway (Holmes et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to correlate the membrane composition of organisms encoding m-PPases, the activity of these enzymes, and their biological role. Holmes, Goldman & Kalli (2022) demonstrated that the lipid environment contributes to intersubunit communication and the current catalytic asymmetry model. For the three proteins studied (from T. maritima , V. radiata, and Clostridium leptum ), the enzymes preferentially interact with anionic lipids rather than with neutral lipids ( Holmes, Goldman & Kalli, 2022 ), which is important given the nature of the organisms that have been found to encode these enzymes, but the environmental conditions under which these organisms thrive are different.…”
Section: Membrane-bound Ppasesmentioning
confidence: 93%
“…Computer multiscale simulations have recently addressed the complexity of these enzymes, and the conserved structure found in m-PPases (the number of transmembrane helices and the number of active site structural transitions) indicates that the lipid microenvironment is a determinant of both catalysis and protein dimeric structure ( Holmes, Goldman & Kalli, 2022 ). Further research is needed to correlate the membrane composition of organisms encoding m-PPases, the activity of these enzymes, and their biological role.…”
Section: Membrane-bound Ppasesmentioning
confidence: 99%
See 1 more Smart Citation
“…global conformational changes should occur in the first 0.1-0.2 s at 20 °C. These need to be tested through functional and structural studies, in particular the use of time-resolved, single-molecule techniques to capture further details of mechanism, as well as efforts to capture mechanistic details through molecular dynamicsefforts that are already underway (Holmes et al, 2022).…”
Section: Ion Selectivitymentioning
confidence: 99%